Implementation of Smoke-Free Are (KTR) Policy in Regional Apparatus Organizations of Merangin Regency - Gustina Putri, Amelia; Ridwan, M.; Rifqi Azhary, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2025)
The government has established a Smoke-Free Area through Law No. 36 of 2009 concerning Health regulating the Smoke-Free Area), which is clarified by PP No. 109 of 2012. However, the implementation of KTR has not been effective, this is indicated by the continued occurrence of violations such as smoking and selling cigarettes in prohibited areas without strict sanctions. The purpose of this study was to determine the implementation of KTR policy. The research method used was a qualitative type with a case study approach involving 12 informants from OPD in Merangin Regency. The results of this study are that the Implementation of KTR is still not optimal. Policy socialization is carried out through communication media, but there has been no special training. Supervision and eval_uation are not in accordance with Regional Regulation, there are no special human resources, facilities and funds are limited, and individual awareness is still low. OPD show commitment through appeals, but there are no incentives from the Health Office. The bureaucratic structure is not yet supportive due to the absence of SOPs and special organizational structures in each OPD. It is recommended that local governments conduct training, allocate special funds and prepare SOP and supervisory teams.